Deteksi Dini Kanker Payudara dengan Teknik SADARI pada Siswi SMK Negeri 1 Tolitoli - Hasni, Hasni; Evie, Sova (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Cancer that is detected early has the possibility to get better treatment. The problem of breast cancer is even bigger because more than 70% of sufferers come to the doctor at an advanced stage, therefore it requires special treatment. Breast cancer can be found early with a BSE examination. BSE is very important because almost 85% of breast lumps are found by sufferers themselves. The purpose of this Community Service is to increase the knowledge of students at SMK Negeri 1 Tolitoli Regency about early detection of breast cancer using the BSE technique. Methods used include lectures, questions, answers, discussions, and demonstrations of BSE techniques. The targets were 55 female students at SMK 1 Negeri 1 Tolitoli. From the results of the post-test carried out, it was found that the average knowledge of female students increased from 40 to 80. As for the behavior in the pretest, it was found that <T Mean became >T Mean during the post-test. It can be concluded that there is an increase in knowledge and behavior changes in female students after education.